SARS-CoV-2 transmission in the Lombardy Region: the increase of household contagion and its implication for containment measures - Signorelli, Carlo; Odone, Anna; Stirparo, Giuseppe; Cereda, Danilo; Gramegna, Maria; Trivelli, Marco; Rezza, Gianni (Acta Biomedica Atenei Parmensis, 2020)
This study aimed at the identification of the settings linked to SARS-CoV-2 transmission through the analysis of clusters and small outbreaks detected by the Lombardy Region surveillance system during the second epidemic wave. Comparing the data before and after the introduction of restrictive measures (night curfew, partial closure of schools and businesses, smaart working), we observed a significant decrease of infections in workplaces, social gatherings, coffee shops, restaurants, and sports centers; contagion in schools decreased from 9.2% to 3.4%, in hospitals environments and nursing homes from 5% to 2%; domestic infections increased instead from 73.5% to 92.7%. These results suggest that containment measures have been effective in controlling virus circulation in the community but not at the household level and might inform future interventions, including the establishment of structures (Covid Hotels) for the isolation infected people. At the same time, they raise awareness on the risk of transmission among family members and during households social gatherings.